Stable and Broad Spectrum Cross-Protection Against Pepino Mosaic Virus Attained by Mixed Infection - Agüero, Jesús; Gómez-Aix, Cristina; Sempere, Raquel N.; García-Villalba, Julio; García-Núñez, Jorge; Hernando, Yolanda; Aranda, Miguel A. (Frontiers in Plant Science, 2018)
While recent pepino mosaic virus (PepMV; species Pepino mosaic virus, genus Potexvirus, family Alphaflexiviridae) epidemics seem to be predominantly caused by isolates of the CH2 strain, PepMV epidemics in intensive tomato crops in Spain are caused by both CH2 and EU isolates that co-circulate, representing a challenge in terms of control, including cross-protection. In this work, we hypothesized that mixed infections with two mild isolates of the EU and CH2 strains (PepMV-Sp13 and -PS5, respectively) may be useful in PepMV cross-protection in Spanish epidemics, providing protection against a broad range of aggressive isolates. Thus, we performed a range of field trials and an experimental evolution assay to determine the phenotypic and genetic stability of PepMV-Sp13 and -PS5 mixed infections, as well as their cross-protective efficiency. Our results showed that: (i) the phenotype of PepMV-Sp13 and -PS5 mixed infections was mild and did not change significantly when infecting different tomato cultivars or under different environmental conditions in Spain, (ii) PepMV-Sp13 and -PS5 mixed infections provided more efficient protection against two aggressive EU and CH2 isolates than single infections, and (iii) PepMV-Sp13 and -PS5, either in single or in mixed infections, were less variable than other two PepMV isolates occurring naturally in PepMV epidemics in Spain.